A Software Defined Radio based UHF Digital Ground Receiver System for Flying Object using LabVIEW - Panda, Amiya Ranjan; Mishra, Debahuti; Ratha, Hare Krishna (Defence Science Journal, 2017)
This study demonstrates the design and implementation of a software defined radio based digital ground receiver system using LabVIEW. In flight testing centre, command transmission system is used to transmit specific commands to execute some operation inside the flight vehicle. One ground receiver system is needed to monitor the transmitted command and monitor the presence of the command in air. The newly implemented ground receiver system consists of FPGA, RTOS and general processing unit. The analog to digital conversion and RF down conversions are carried out in high speed PCI extension for instrumentation express cards. The communication algorithms, digital down conversion are implemented in FPGAs. The communication system uses digital demodulation and decoding scheme and realised by NI PXI-7966R with Xilinx Virtex 5, SXT, FPGA. The performance of the receiver system has been analysed by linearity measurement of pre-amplifier Gain, Noise figure, frequency, power and also measurement of sensitivity. The results show successful implementation of the ground receiver system.